2013
DOI: 10.1105/tpc.112.106385
|View full text |Cite
|
Sign up to set email alerts
|

Orchestration of Thiamin Biosynthesis and Central Metabolism by Combined Action of the Thiamin Pyrophosphate Riboswitch and the Circadian Clock in Arabidopsis    

Abstract: Riboswitches are natural RNA elements that posttranscriptionally regulate gene expression by binding small molecules and thereby autonomously control intracellular levels of these metabolites. Although riboswitch-based mechanisms have been examined extensively, the integration of their activity with global physiology and metabolism has been largely overlooked. Here, we explored the regulation of thiamin biosynthesis and the consequences of thiamin pyrophosphate riboswitch deficiency on metabolism in Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
205
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(227 citation statements)
references
References 73 publications
(101 reference statements)
20
205
2
Order By: Relevance
“…First, it appears that a single point mutation in the THI4 riboswitch is sufficient to considerably increase B 1 vitamer levels in this alga. This is significant because a recent study in the model plant Arabidopsis showed that the equivalent mutation in the THIC riboswitch affects only the TMP levels, with a threefold change (31). In our study on Chlamydomonas, all three vitamers are increased 5-10-fold (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…First, it appears that a single point mutation in the THI4 riboswitch is sufficient to considerably increase B 1 vitamer levels in this alga. This is significant because a recent study in the model plant Arabidopsis showed that the equivalent mutation in the THIC riboswitch affects only the TMP levels, with a threefold change (31). In our study on Chlamydomonas, all three vitamers are increased 5-10-fold (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Recent studies on thiamine metabolism in photosynthetic organisms have revealed complex regulatory mechanisms involving a riboswitch located on the ThiC pre-mRNA and the presence of regulatory elements located in the 59 upstream sequence of this gene responsible for circadian control of transcription (Bocobza et al, 2013). In addition, a link between stimulation of thiamine biosynthesis under stress and the induction of mRNA for TK and other TPP-requiring enzymes was recently reported (Rapala- Kozik et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This could simply be a consequence of the slow-growth phenotype of these plants. However, starch and chlorotic phenotypes have been observed in plants with altered thiamine metabolism, even in those where growth was not reduced and that possessed an increased capacity for TPP biosynthesis (Bocobza et al, 2013). Plants expressing a ThiC gene with a mutated riboswitch that was insensitive to TPP had starch grains with altered structure, suggesting a change in the process of starch biosynthesis.…”
Section: Tkox Plants Display Compromised Carbon Allocation To the Isomentioning
confidence: 99%
“…This negative feedback regulation of thiamine biosynthesis at the AS level ensures a high level of transcripts under low cellular TPP concentrations. Plants expressing THIC with a disrupted TPP riboswitch in a thic mutant showed growth retardation, chlorosis, and delayed flowering, indicating the physiological significance of riboswitch-mediated regulation of THIC (Bocobza et al, 2013). It is not known to what extent riboswitches regulate AS of other pre-mRNAs in plants.…”
Section: Regulation Of As By Secondary Structuresmentioning
confidence: 99%